ANALISIS PRODUKTIVITAS MAHASISWA INSTITUT AGAMA ISLAM (IAI) NUSANTARA BATANGHARI MELALUI PEMBELAJARAN ONLINE - Yusup, Muhammad; Marzani, Marzani (UIN Imam Bonjol Padang, 2020)
This paper is motivated by the conditions of learning during the Covid-19 pandemic. The learning process must be done from home. In accordance with government policy, work from home and learn from home. The purpose of this research is to study the creativity of students in implementing online learning during the Covid-19 pandemic. The research method used is using a qualitative method with descriptive analysis. And as respondents and sources of data for this study were students of IAI Nusantara Batanghari. The results showed as many as 79.4% thought online learning was very effective, while 20.6% thought it was not yet effective. That means effectiveness can increase student productivity. This result is supported by data as much as 23% they strongly agree, 44% agree, and there are 15% of students who disagree. It shows the quality of online learning, increases student productivity, both increases productivity in soft skill development and self-development increases business efficiency in meeting daily needs.